PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU POST SECTIO CAESAREA DI RUMAH SAKIT MITRA HUSADA TANGERANG - Wira Nanda, Prima; Wardiah (Jurnal Ilmiah Kesehatan BPI, 2025)
View the part of the body that is experiencing problems and ends with stitching the wound. Risks for post-cesarean section patients include impaired mobility, risk of infection, risk of bleeding, post-cesarean discomfort. At Mitra Husada Hospital, Tangerang, in 2022, 181 caesarean section patients were found in the room. Meanwhile, in 2023 there will be 153 caesarean section patients. This study aims to analyze the effect of deep breathing relaxation techniques on the intensity of maternal pain during post caesarean section at Mitra Husada Hospital, Tangerang. Research Method: using a quantitative approach with the Quasy experimental method with a one group pretest - post test design. It is used because the population of women post Sectio Cesaria in the obstetrics treatment room is known to be large. The sample in this study was 60 people using the Slovin formula technique. Results: The results of the average decrease in the mean before and after the deep breathing relaxation technique were carried out obtained a value of 30.50. pain before the breath relaxation technique was found by respondents experiencing 7-10 Severe pain as many as 39 (65.0%) respondents and pain after the breath relaxation technique was obtained by the majority with 11-3 mild pain as many as 32 (53.3%) respondents. The non- parametric statistical test Wilcoxon test, found a Wilcoxon value of -7.239 and a P-Value of 0.000 or <0.05, which means that H0 is rejected and Ha is accepted. It can be concluded that there is a significant effect of deep breathing relaxation techniques on reducing pain intensity in post-section mothers. caesarean section at Mitra Husada Hospital, Tangerang.